The Relationship of Full Day School Policy And Interest in Learning to Science Learning Outcomes in Grade IV At SD Negeri 04 Batang Tajongkek Padang Pariaman - Elva Revariza; Dwi Hadita Ayu; Nur Aisyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research is motivated by the low learning outcomes of students, particularly in the subject of IPAS, due to the implementation of a full day school policy and students' lack of interest in participating in lessons at Fourth Grade SD Negeri 04 Batang Tajongkek. Based on this background, the aim of this study is to determine the relationship between the full day school policy and students' learning interest on IPAS learning outcomes in Fourth Grade SD Negeri 04 Batang Tajongkek. This research is a correlational study with both simple and multiple correlation types. The research sample consists of 25 students. The instruments used are closed questionnaires to measure the variables of full day school policy and learning interest to describe IPAS learning outcomes in Fourth Grade SD Negeri 04 Batang Tajongkek. Data analysis techniques include descriptive statistical analysis and hypothesis testing. The results indicate a relationship between the full day school policy and learning interest with IPAS learning outcomes in Fourth Grade SD Negeri 04 Batang Tajongkek. The analysis showed a simple and multiple hypothesis test, with a correlation coefficient for the full day school policy (rx_1y) of 0.39, indicating a correlation with a contribution of 15.21% of the full day school policy variable to student learning outcomes, which is significant (t_calculated 2.188 > t_table 2.069, at α=0.05). The correlation coefficient for learning interest (rx_2y) is 0.42, indicating a correlation with a contribution of 17.64% of the learning interest variable to learning outcomes, which is significant (t_calculated 2.208 > t_table 2.069, at α=0.05). The multiple correlation coefficient for the full day school policy and learning interest with learning outcomes is rx_1 x_2y = 0.74, showing a strong correlation with a contribution of 54.76% from both variables to learning outcomes, which is significant (F_calculated 13.35 > F_table 2.074, at α=0.05). Thus, there is a relationship between the full day school policy and learning interest with IPAS learning outcomes in Fourth Grade SD Negeri 04 Batang Tajongkek.